Quantitative Characterization of Liver Safety in Surgical Diseases and Postoperative Course: Karakterisasi Kuantitatif Keamanan Hati pada Penyakit Bedah dan Perjalanan Pascaoperasi - Akhmedov M. Dj; Askarov T.A; Fayziev Y.N.; Ashurmetov A.; Ismailov F. M. (Academia Open, 2026)
General Background: Accurate assessment of liver functional reserve remains critical in surgical practice, as hepatic dysfunction substantially elevates postoperative morbidity and mortality risks. Specific Background: Conventional biochemical markers (ALT, AST, bilirubin) predominantly reflect cytolysis and cholestasis but fail to evaluate hepatocellular energetic status or regenerative capacity. Knowledge Gap: Current diagnostic approaches lack objective quantitative indicators that directly measure mitochondrial function and viable hepatocyte populations in surgical patients. Aims: This study evaluated a novel prognostic coefficient based on the ratio of cytochrome C to TMPD oxidase mitochondrial activities for quantifying liver parenchymal preservation in patients with hepatobiliary surgical diseases. Results: Analysis of 24 patients demonstrated strong inverse correlation between coefficient values and viable hepatocyte percentages. Coefficients of 2.5-3.5 units indicated favorable prognosis, 5-7 units signaled elevated complication risk, while values ≥8 units predicted unfavorable outcomes, irrespective of standard biochemical parameters. Novelty: Unlike traditional markers, this coefficient directly reflects mitochondrial respiratory chain integrity and hepatocellular viability through objective biochemical measurements. Implications: The proposed coefficient serves as an integrated quantitative marker of hepatic functional reserve, enabling improved surgical risk stratification and outcome prediction in hepatobiliary surgery.Highlight : The cytochrome C to TMPD oxidase ratio correlates better with hepatocyte viability than standard biochemical markers in both experimental and clinical contexts. Coefficient values predict postoperative outcomes: 2.5-3.5 units indicate favorable prognosis, 5-7 units suggest complications, and ≥8 units correlate with mortality. Mitochondrial dysfunction demonstrates universal quantifiable patterns across different etiologies, showing consistent relationships between the coefficient and hepatocyte viability. Keywords :Liver Functional Reserve, Mitochondrial Dysfunction, Cytochrome C Oxidase, Hepatocyte Viability, Postoperative Prognosis